Genetic Variability in Indigenous Brinjal Land Races of Dimapur District of Nagaland and their Traditional Cultivation Practices - Bhagowati, Raktim Ranjan; Changkija, Sapu (International Journal of Bio-resource and Stress Management, 2010)
Generally significant genetic variability is observed in the £ available brinjal land races found in the low altitude growing areas in the state of Nagaland, India. They possess several unique characteristics of plant breeding importance with enough scope for further improvement to suit the traditional growing conditions of the state. Many of these land races also show good genetic resistance and/or tolerance to some biotic stresses. Therefore, the land races could also serve as good source of resistance or tolerance in plant breeding programs. This present study reports a large variability of land races in high land of Nagaland. There is enormous potentials of semi-perennial races and the immature fruits also possess certain medicinal properties as per the traditional belief. Systematic documentation and preservation of these valuable germplasm resources need immediate attention of scientific communities of the country. In the present investigation the genetic variability with respect to certain economic traits in a few traditional land races of brinjal in Dimapur district of Nagaland were studied